\[\boxed{\text{421\ (421).}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[x = 6a + 3;\ \ \ y = 6b + 2:\]
\[xy = (6a + 3) \cdot (6b + 2) =\]
\[= 36ab + 12a + 18b + 6 =\]
\[= 6 \cdot (6ab + 2a + 3b + 1) -\]
\[делится\ нацело\ на\ 6.\ \]
\[Что\ и\ требовалось\ доказать.\]
\[\boxed{\text{421.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ \left( 2a^{2} - 5a + 7 \right) + \ *\ = 5\]
\[* = 5 - \left( 2a^{2} - 5a + 7 \right)\]
\[* = 5 - 2a^{2} + 5a - 7\]
\[* = - 2a^{2} + 5a - 2.\]
\[2)\ \left( 2a^{2} - 5a + 7 \right) + \ * = 0\]
\[* = 0 - \left( 2a^{2} - 5a + 7 \right)\]
\[*\ = 0 - 2a^{2} + 5a - 7\]
\[*\ = - 2a^{2} + 5a - 7.\]
\[3)\ \left( 2a^{2} - 5a + 7 \right) + \ *\ = a^{2}\]
\[*\ = a^{2} - (2a^{2} - 5a + 7)\]
\[*\ = a^{2} - 2a^{2} + 5a - 7\]
\[*\ = - a^{2} + 5a - 7.\]
\[4)\ \left( 2a^{2} - 5a + 7 \right) + \ *\ = - 2a\]
\[*\ = - 2a - \left( 2a^{2} - 5a + 7 \right)\]
\[*\ = \ - 2a - 2a^{2} + 5a - 7\]
\[* = - 2a^{2} + 3a - 7\text{.\ }\]